Pharmacology and Toxicology of Amphetamine-Type Stimulants - João Paulo Capela; Vera Marisa Costa (MDPI AG, 2023)
Amphetamine-type stimulants are drugs chemically related to the natural compounds ephedrine and cathinone [...]